Periodontal treatment during pregnancy decreases the rate of adverse pregnancy outcome: a controlled clinical trial - Adriana Campos Passanezi Sant'Ana; Marinele R. de Campos; Selma Campos Passanezi; Maria Lúcia Rubo de Rezende; Sebastião Luiz Aguiar Greghi; Euloir Passanezi (University of São Paulo, 2011)
OBJECTIVES: The aim of this study was to evaluate the effects of non-surgical treatment of periodontal disease during the second trimester of gestation on adverse pregnancy outcomes. MATERIAL AND METHODS: Pregnant patients during the 1st and 2nd trimesters at antenatal care in a Public Health Center were divided into 2 groups: NIG - "no intervention" (n=17) or IG- "intervention" (n=16). IG patients were submitted to a non-surgical periodontal treatment performed by a single periodontist consisting of scaling and root planning (SRP), professional prophylaxis (PROPH) and oral hygiene instruction (OHI). NIG received PROPH and OHI during pregnancy and were referred for treatment after delivery. Periodontal evaluation was performed by a single trained examiner, blinded to periodontal treatment, according to probing depth (PD), clinical attachment level (CAL), plaque index (PI) and sulcular bleeding index (SBI) at baseline and 35 gestational weeks-28 days post-partum. Primary adverse pregnancy outcomes were preterm birth (<37 weeks), low birth weight (<2.5 kg), late abortion (14-24 weeks) or abortion (<14 weeks). The results obtained were statistically evaluated according to OR, unpaired t test and paired t test at 5% signifcance level. RESULTS: No signifcant differences were observed between groups at baseline examination. Periodontal treatment resulted in stabilization of CAL and PI (p>0.05) at IG and worsening of all periodontal parameters at NIG (p<0.0001), except for PI. Signifcant differences in periodontal conditions of IG and NIG were observed at 2nd examination (p<0.001). The rate of adverse pregnancy outcomes was 47.05% in NIG and 6.25% in IG. Periodontal treatment during pregnancy was associated to a decreased risk of developing adverse pregnancy outcomes [OR=13.50; CI: 1.47-123.45; p=0.02]. CONCLUSIONS: Periodontal treatment during the second trimester of gestation contributes to decrease adverse pregnancy outcomes.